Near-Infrared Luminescence from Visible-Light-Sensitized Ruthenium(II)-Neodymium(III) Heterobimetallic Bridged Complexes Containing Alkoxy(silyl) Functional Groups - Sábio, Rafael M. [UNESP]; Santagneli, Silvia H. [UNESP]; Gressier, Marie; Caiut, José M.A.; Pazin, Wallance M.; Silva, Robson R.; Ribeiro, Sidney J.L. [UNESP]; Menu, Marie-Joëlle (Sociedade Brasileira de Quimica (SBQ), 2020)
New infrared emitting d-f (ruthenium(II)–neodymium(III)) heterobimetallic complexes with alkoxy(silyl) functional groups have been prepared. Visible excitation evidenced energy transfer processes from the ruthenium(II) donor to neodymium(III) acceptors leading to infrared emission. Energy transfer rates (kEnT) and efficiency of energy transfer (ηEnT) are, respectively, 0.61 × 107 s-1 and 44% for RuL1–NdL3 complex. Larger values of kEnT (3.04 × 107 s-1) and ηEnT (84%) were detected for RuL2–NdL4 complex. RuL1–NdL3 and RuL2–NdL4 complexes were fully characterized by elementary analysis (EA), mass spectrometry (MS), Fourier transform infrared spectroscopy (FTIR) and Fourier transform Raman spectroscopy (FT-Raman). Total correlation spectroscopy (TOCSY1D), 1H{13C} heteronuclear single quantum correlation (HSQC) and 1H{13C} heteronuclear multiple bond correlation (HMBC) nuclear magnetic resonance (NMR) analyses were also carried out to characterize NdL3 and RuL1–NdL3 complexes. The presence of trialkoxysilyl-substituted ligands would allow further grafting onto any silica or silicated surface aiming at applications as new luminescent near infrared (NIR)-emitting biosensors or biomarkers.
Keywords: D-f energy transfer; Grafting trialkoxysilyl group; Neodymium(III); NIR luminescent complexes; Ruthenium(II); Silylated heterobimetallic complexes; Visible